Family Communication as a Prevention Effort Early Marriage in Pegantenan Village, Madura - Nikmah Suryandari; Irya Nur Holifah (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study is to find out family communication as an effort to prevent early marriage in Pegantenan Village Pamekasan Madura. The study subjects were families in Pegantenan Village with children under the age of 20 who were unmarried. This research was qualitative. Data collection methods used observations and interviews and documentation. Informants were selected using the purposive sampling method. Data analysis used data reduction, data presentation, and data verification (conclusions). Data validity examination technique used triangulation techniques. The results showed that families in Pegantenan Village of Pegantenan District of Pamekasan Regency used 2 (two) models of family communication, namely consensual family communication, which often emphasizes communication, and is protective because decision making is dominated by parents. The conclusion of this study showed that economic, cultural, and lack of awareness about reproduction were the main factors of early marriage in Pegantenan Madura Village.Keywords: Family communication, early marriage, Pegantenan village, Madura ABSTRAKTujuan penelitian ini adalah untuk mengetahui komunikasi keluarga sebagai upaya pencegahan pernikahan dini di Desa Pegantenan Pamekasan Madura. Subjek penelitian adalah keluarga di Desa Pegantenan dengan anak di bawah usia 20 tahun yang belum menikah. Penelitian ini adalah penelitian kualitatif. Metode pengumpulan data menggunakan observasi dan wawancara serta dokumentasi. Informan dipilih dengan menggunakan metode purposive sampling. Analisis data menggunakan reduksi data, penyajian data, dan verivikasi data (kesimpulan). Teknik pemeriksaan keabsahan data menggunakan teknik triangulasi. Hasil penelitian menunjukkan bahwa keluarga di Desa Pegantenan Kecamatan Pegantenan Kabupaten Pamekasan menggunakan 2 (dua) model komunikasi keluarga, yaitu komunikasi keluarga konsensual, yang menekankan seringnya terjalin komunikasi, dan protektif karena pengambilan keputusan didominasi oleh orang tua. Simpulan dari penelitian ini menunjukkan bahwa factor ekonomi, budaya, dan kurangnya kesadaran tentang reproduksi menjadi factor utama terjadinya pernikahan dini di Desa Pegantenan Madura.Kata Kunci: Komunikasi keluarga, pernikahan dini, Desa Pegantenan; Madura